The Flint Hills—Place and Thin Places: Creativity and Connection - H. C. Palmer (Symphony in the Flint Hills, 2012)
How the Flint Hills and the prairie impacted the life of poet and writer H.C. Palmer.
Keywords: Kansas; creativity; Camp Wood; Vietnam; story; art; native; grass; grassland; tallgrass; war; celebration; nature; natural